The practice of green Tara - Ven. Bardor Tulku Rinpochoe (New York : Rinchen Publications, 1999)
"This teaching is on the deity called Arya Tara. If we examine the nature of Arya Tara from the point of what is called the definitive meaning, the true meaning, then she is Yum Chen Mo, the Great Mother. Arya Tara is called the Great Mother because she embodies the ultimate meaning of dharma, the ultimate meaning of emptiness - the dharmakaya. The ultimate meaning of dharma is like a mother in the sense that it is the source from which buddhas obtain enlightenment and bodhisattvas obtain realization. The dharmakaya is what gives rise to, or gives birth to all buddhas and bodhisattvas. Therefore, this ultimate meaning of the dharma, which is the dharmakaya, is called Yum Chen Mo, the Great Mother."